Jenis Pakan yang Berbeda terhadap Performa Benih Arwana Silver Albino (Osteoglossum bicirhosum) - Sarmila Sarmila; Agus Setiawan; Hylda Khairah Putri; Susilawati Susilawati; Farid Mudlofar; Ridwan Salim; Sri Warastuti (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
Albino Silver Arowana (Osteoglossum bicirrhosum) is one of the most popular freshwater ornamental fish commodities alongside Super Red Arowana fish. This is because the price is affordable compared to the original Indonesian Arowana type. Albino Silver Arowana cultivation activities in Indonesia have begun to develop, but information on suitable feeds to support performance is poorly studied. This study aimed to determine the right type of feed to provide the best growth rate and survival rate for albino silver Arowana seeds. The albino silver Arowana seeds used in this study had an average size of 7. cm as many as 72 individuals. Seed maintenance was carried out for 40 days. This study used a completely randomized design (CRD), with 4 treatments and 3 replications. Treatment A used Kroto (Oecophylla smaragdina), treatment B used rebon shrimp (Mysis relicta), treatment C used yellow mealworm (Tenebrio Molitor), and treatment K used bloodworm (Chironomus sp.). Seed growth rate data were collected at the end and beginning of maintenance. Observation of the survival rate of seeds was carried out every day. The data obtained were tabulated and statistical analysis was performed (ANOVA). The results showed that the sources given in treatment K and treatment A had the highest growth compared to those in treatment B and treatment C.